Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Teknik Dasar Servis Pendek Bulutangkis - Yauma Ruqy Ramdan Hidayat; Balkis Ratu N L Esser; Elya Wibawa Syarifoeddin; Intan Primayanti (Universitas Hamzanwadi, 2026)
The problem addressed in this study is that Physical Education (PJOK) instruction in high schools is still dominated by a conventional, teacher-centered model, resulting in students being less active and less motivated, and suboptimal learning outcomes in the basic short serve technique in badminton. This study aims to improve learning outcomes in the short serve technique in badminton through the STAD cooperative learning model STAD cooperative learning model. The research method used was the Kemmis & McTaggart Classroom Action Research model, conducted in two cycles with 35 tenth-grade students at SMAN 1 Gunungsari. The instruments included observation sheets and short serve practice tests. Data analysis used quantitative descriptive statistics. The results showed that in Cycle I, the average score was 51.96 with a classical mastery rate of 20% (7 students). In Cycle II, the average score increased to 72.70 with a mastery rate of 80% (28 students). The average score increased by 20.74 points, and the mastery rate rose by 60%. All students demonstrated active participation and good cooperation within their groups. In conclusion, the STAD cooperative learning model is effective in improving the learning outcomes of basic short serve techniques in badminton for 10th-grade students at SMAN 1 Gunungsari.